2015
DOI: 10.47253/jtrss.v3i1.685
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Carbon Pools in Dipterocarp Forests of Peninsular Malaysia

Abstract: Modification and loss of forests due to natural and anthropogenic disturbances contribute an estimated 20% of annual greenhouse gas (GHG) emissions worldwide. Accounting GHG emissions associated with forestry, specifically, and land use generally is crucial in recent days because forests play major roles in balancing terrestrial carbon and contribute to the mitigation of global warming and climate change. Consequent to the awareness of climate change, reducing emission from deforestation and forest degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…In Malaysia, Raihan et al [112] reported higher AGB-Cstocks than BG-Cstocks. In support of the findings of this study, Omar et al [113] and Matthew et al [114] found higher contents of aboveground carbon than belowground carbon, with net differences of at least 60%. A study in Zambia by Pelletier et al [101] affirmed that the biomass gains and carbon sink were concentrated in several dominant species, including the Fabaceae, which is a subfamily of Caesalpinioideae, although some dominant species showed threats of overexploitation.…”
Section: Carbon Stocks and Other Variables Associated With Forest Bio...supporting
confidence: 88%
See 1 more Smart Citation
“…In Malaysia, Raihan et al [112] reported higher AGB-Cstocks than BG-Cstocks. In support of the findings of this study, Omar et al [113] and Matthew et al [114] found higher contents of aboveground carbon than belowground carbon, with net differences of at least 60%. A study in Zambia by Pelletier et al [101] affirmed that the biomass gains and carbon sink were concentrated in several dominant species, including the Fabaceae, which is a subfamily of Caesalpinioideae, although some dominant species showed threats of overexploitation.…”
Section: Carbon Stocks and Other Variables Associated With Forest Bio...supporting
confidence: 88%
“…In Malaysia, Raihan et al [112] reported higher AGB-Cstocks than BG-Cstocks. In support of the findings of this study, Omar et al [113] and Matthew et al [114] found higher contents of aboveground carbon than belowground carbon, with net differences of at least 60%. In contrast to the findings of this study, Xu et al [111] reported higher carbon stocks belowground when compared with the aboveground content.…”
Section: Carbon Stocks and Other Variables Associated With Forest Bio...supporting
confidence: 88%